Growth, herbage accumulation, and nutritive value of ‘tifton 85' bermudagrass as affected by nitrogen fertilization strategies - Borges, Bernardo M. M. N. [UNESP]; Silveira, Maria L.; Cardoso, Saulo S. [UNESP]; Moline, Ederlon F. V. [UNESP]; Coutinho Neto, Andre M. [UNESP]; Lucas, Fabio T. [UNESP]; Muraoka, Takashi; Coutinho, Edson L. M. [UNESP] (Wiley, 2017)
Nitrogen fertilization affects ‘Tifton 85' bermudagrass (Cynodon spp.) herbage accumulation (HA) and nutritive value; however, forage response may be affected by N fertilizer source, application levels, and environmental conditions. This 2-yr study evaluated the effect of different N fertilization strategies on Tifton 85 bermudagrass responses in a tropical soil from southeast Brazil. Treatments were two N sources (ammonium nitrate [AN] and urea) applied at 0, 60, 120, 180, and 240 kg N ha-1 harvest-1. Fertilizer sources were enriched with 15N to quantify the recovery of fertilizer-derived N. Forage was harvested at 30-d intervals to evaluate HA and shoot N concentration. Leaf area index (LAI), intercepted photosynthetically active radiation (PARi), and chlorophyll index were measured 1 d before harvest. Ammonium nitrate and urea resulted in similar Tifton 85 HA. Maximum Tifton 85 HA (4.6 Mg ha-1 ) was reached at the fertilization level of 210 kg N ha-1 harvest-1 while critical shoot N concentration, herein defined at 90% relative production, was 23.7 g kg-1. Similarly, critical PARi and LAI were 71% and 4.7 m2 m-2, respectively. Nitrogen recovery in the plant and soil was greater for urea (52%) than AN (41%). Despite the relatively greater shoot N accumulation, N recovery decreased as N levels increased. Nitrogen application level should be adjusted to optimize HA, nutritive value, and N recovery.